Automatic Headline Generation for Hindi News using Fine-tuned Large Language Models - Kumar, Jeetendra; Shekhar, Shashi; Gupta, Rashmi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Generating news headlines is one use case for automated text summarization. With only a few text lines, it creates a summary of the longer content, cutting down on reading time. Text summarization is a very challenging task and it is very difficult to generate summaries as a human being. Most summary tools available in the market primarily concentrate on summarizing English material, resulting in a scarcity of summarizers for other languages. In this study, we used two datasets gathered from Dainik Bhaskar, NavBharat Times, and one publically available dataset to fine-tune four pre-trained language models: Someman/bart-hindi, facebook/mbart-large-50, indicBART, and mT5. To conduct a full performance assessment, a variety of evaluation metrics are utilized. Our comprehensive examination consistently reveals that the facebook/mbart-large-50 model exhibits superior performance compared to other models in terms of these metrics. This highlights its potential to enhance automated summarization systems and facilitate enhanced content retrieval and comprehension within the Hindi-speaking community.